Barriers to the Implementation of the Amsterdam 2022 Statement in the Secondary School Setting - Luis Torres; Jennifer Baldari; Frederick Gardin; August Price (Journal of Sports Medicine and Allied Health Sciences: Official Journal of the Ohio Athletic Trainers' Association)
Introduction: Athletic trainers are reasonably expected to evolve their concussion management protocols to better align themselves with the recommendations found in the Amsterdam 2022 Statement. Secondary school athletic trainers may lack the time, training, or resources to actualize these recommendations within their protocols. The purpose of this study was to identify the barriers associated with the implementation of the Amsterdam 2022 Statement recommendations in the secondary school setting. Methods: 89 secondary school ATs (44 males, 45 females) in the NATA District 1 and District 2 regions were provided with an electronic survey using Qualtrics (Qualtrics, Provo, UT), consisting of 6 demographic items (i.e., sex, race/ethnicity, initial entry-level AT education, highest level of education, years of AT experience, and state of current practice) and 11 items related to details on their currently existing concussion management protocols, their familiarity with the new recommendations in the Amsterdam 2022 Statement, and their ability and willingness to update their concussion management protocols as needed. Results: Only about half of the athletic trainers (52.11%) in this study agreed that their current protocols aligned themselves with the latest recommendations despite these recommendations being publicly available to the sports medicine community for over a year at the time of this study. Reported barriers to implementation ranged from a lack of support from relevant stakeholders to a lack of awareness or resources pertaining to the use of the SCAT6 or the new RTS progressions. Conclusion: Organizational administrators can further facilitate the implementation process by providing practical support, especially as it relates to environmental, policy, and financial resources. In addition to the provision of support, continuing education on the topic of SRC needs to remain a focal point in the athletic training profession to reduce the delay that exists between the discovery of well-researched best practice recommendations to the utilization of these recommendations in active practice.